Capturing better photos & video with your iPhone - Thomas, J. Dennis (Hoboken, N.J. : Wiley, 2011)
A guide to capturing photographs and video with the iPhone covers such topics as resolution, lighting, apps, composition, and editing-
Includes bibliographical references and index.
Keywords: iPhone (Smartphone); Photography -- Digital techniques -- Amateurs' manuals; Video recording -- Amateurs' manuals; Digital photography; Video recording; iPhone (Smartphone)